Soundness Rating of Commercial Banks Before and After Implementation of RGEC Method in Indonesia - Andriyani, Ima; Mayasari, Rosalina Pebrica; Aryani, Dwi Septa (UNIVERSITY OF MERDEKA MALANG, 2018)
This research aims to analyze the differences in the soundness of commercial banks before and after the implementation of the Risk Profile, Good Corporate Governance, Earning, Capital (RGEC) method in Indonesia. The unit of the analysis was a commercial bank with a purposive sampling method of 10 banks. The study period was 2008-2016. Data analysis technique was using comparative test with the different test of t-test for the related sample. Hypothesis testing with paired sample t-test and data processing with SPSS 24. The research findings showed that the research model based on the F test is fit so that the model formed can be used to test the difference of soundness level of commercial banks. Referring to each RGEC variable, it was found that the risk profile proxy with a Non-performing loan (NPL) and earning with proxy Net Interest Margin (NIM) not significant before and after RGEC implementation while Good Corporate Governance(GCG) and Capital Adequacy Ratio (CAR) have significant difference before and after the implementation of RGEC. This study for GCG testing still used self-assessment which can be seen from the score of each bank directly.JEL Classification: G21; G34DOI:Â https://doi.org/10.26905/jkdp.v22i1.1549